Observations of a Medieval Quantitative Historian? - Romanov, Maxim (Der Islam, 2017)
A comparison of the results of the computational analysis of the Taʾrīkh al-islām, al-Dhahabī’s 50-volume biographical collection, with brief statements that describe the rise and decline of cities and provinces of the Islamic world with the al-Amṣār dhawāt al-āthār, al-Dhahabī’s 4-folio epistle, suggests that al-Dhahabī had a solid grasp of the tremendous amount of biographical and historical data that he collected, and that his short epistle may be regarded as a missing analytical summary of the most ambitious historical project in the pre-modern Islamic world. In light of these results, we perhaps may think of al-Dhahabī as one of the earliest quantitative historians. Although we do not have conclusive evidence about how exactly al-Dhahabī worked with his data, the paper argues that all necessary mathematical, visual and ‘mechanical’ techniques that would facilitate data analysis already existed, and that al-Dhahabī and other premodern Islamic historians could have used them.